Size Matters in Legal Ethics: Contrasting Mediating Mechanisms of Reputational Capital - Raja Frans; Erico Hamdani; Dadan Abdul Aziz Mubarok; Nunung Ayu Sofiati (Yayasan Multidimensi Kreatif, 2026)
The efficacy of digital signaling in credence goods markets remains paradoxical: while visibility tools are universal, their reputational impact is highly context-dependent. This study challenges the prevailing